The Implementation of Project-Based Learning’s Speaking Skill for Tenth Grade Vocational High School Students - Kusumawati, Iin (Soegijapranata Catholic University, 2019)
Project-Based Learning (PBL) is one of strategies which English teachers use in teaching oral activities. The activities which can be implemented in PBL are discussion, conversation, presentation (individual or group), role-play, and others. It also can be an aid in studying and teaching. Based on previous research, using PBL technique can improve students’ speaking ability for second graders of SMPN 1 Kawedanan, Magetan by Permatasari (2013). Because of that, the researcher implements the teaching of speaking using PBL at SMK Dian Indonesia, Sidoarjo. The descriptive qualitative is used as a design of this research. The subject of the research is 20 first-grade students of nursery class, from the academic year 2015/2016. There are three instruments used to collect the data. First is the documentation of related lesson plan and syllabus, second is the observation of field-notes, third is a questionnaire for the students. PBL in teaching speaking is found helpful to regulate students’ ideas and stimulates the group presenter to extend the statement using their own words. PBL was interesting for them, because the researcher gives occasion for them to choose their own topics. They found themselves interested, happy, joyful, and comfortable during the implementation of the PBL because the process of teaching and learning is designed appropriately with the students’ ideas. To gain an effective teaching speaking using PBL, students needed to be active in making collaborative discussions, and giving feedbacks to each other, so that they can build social relationship. The PBL activities have made students build knowledge and think critically.